Reformulasi Sastra Piwulang sebagai Alternatif Baru Model Pendidikan Karakter di Indonesia (Sutasoma : Jurnal Sastra Jawa, 2022)
Character education is the main basis for complete human development. For the Indonesian people, character education is a manifestation of the nation's conscience that must be understood through the existence of daily life experiences. In the repertoire of Javanese literature there is a genre of piwulang literature that was born because of the practical need for character education in the Javanese court environment in the 19th century. The values ​​of character education that were built at that time continue to be embedded in the life of the Javanese people to this day. This fact would be a strong reason for the effort to reformulate piwulang literature as a new alternative model of character education in Indonesia. The approach used in this research is a text phenomenological approach with van Dijk's theory of critical discourse analysis about discourse and its social cognition relations. From the results of a study of piwulang literary texts, it is concluded that the syntactic structure of didactic texts leads to strengthening the sense of taste which in Javanese terms is referred to as "rasa sejati". The essence of taste values ​​include: bekti (respect), tresna (love), and andhap asor (polite). The teaching formulation is in the knowledge of things related to ala-becik, adat-waton, and manners. These three are the essence of character education that is very relevant to be applied today. Keywords: Character education; Serat Wulangreh; critical discourse